Linking brand and competitive advantage: The mediating effect of positioning and market orientation - Orlando Manuel Martins Marques de Lima Rua; Catarina Santos (European Research on Management and Business Economics (ERMBE), 2022)
The purpose of this paper is to analyze the relationship between brand and competitive advantage (through differentiation) and the mediating effect of positioning and market orientation in this relationship. An empirical study was developed using a quantitative methodological approach. The object of the study was Portuguese exporting companies in the footwear industry, to which a questionnaire survey was applied. The results show that (1) brand has a significant direct impact on positioning and market orientation and competitive advantage through differentiation, (2) competitive advantage through differentiation is directly impacted by positioning, (3) market orientation does not have a significant direct impact on competitive advantage through differentiation, and (4) positioning has a mediating effect on the relationship between brand and competitive advantage through differentiation, and market orientation does not have on it.
Keywords: M31; M10; 650; Brand; Competitive advantage; Market orientation; Positioning